2006
DOI: 10.1111/j.1365-3091.2006.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

A sequence stratigraphic model for an intensely bioturbated shallow‐marine sandstone: the Bridport Sand Formation, Wessex Basin, UK

Abstract: The Bridport Sand Formation is an intensely bioturbated sandstone that represents part of a mixed siliciclastic‐carbonate shallow‐marine depositional system. At outcrop and in subsurface cores, conventional facies analysis was combined with ichnofabric analysis to identify facies successions bounded by a hierarchy of key stratigraphic surfaces. The geometry of these surfaces and the lateral relationships between the facies successions that they bound have been constrained locally using 3D seismic data. Facies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(89 citation statements)
references
References 47 publications
1
88
0
Order By: Relevance
“…The Bridport Sand Formation is dominated by bioturbated storm-event beds with calcite-cemented bioclastic lag horizons, which were deposited in an offshore transition to lower shoreface environment. These strata form 10-40 m thick, upward-shallowing units that overlie laterallyextensive, mudstone-rich horizons (Morris et al, 2006). The Down Cliff Clay Member comprises calcareous bioturbated mudstones that record deposition in an offshore transition to offshore environment (Morris et al, 2006).…”
Section: Example 2: Bridport Sand Formation Subaerial Delta and Down mentioning
confidence: 99%
See 1 more Smart Citation
“…The Bridport Sand Formation is dominated by bioturbated storm-event beds with calcite-cemented bioclastic lag horizons, which were deposited in an offshore transition to lower shoreface environment. These strata form 10-40 m thick, upward-shallowing units that overlie laterallyextensive, mudstone-rich horizons (Morris et al, 2006). The Down Cliff Clay Member comprises calcareous bioturbated mudstones that record deposition in an offshore transition to offshore environment (Morris et al, 2006).…”
Section: Example 2: Bridport Sand Formation Subaerial Delta and Down mentioning
confidence: 99%
“…The Down Cliff Clay Member comprises calcareous bioturbated mudstones that record deposition in an offshore transition to offshore environment (Morris et al, 2006). 2D and 3D seismic data calibrated with wells from the onshore Wytch Farm Field indicate that each upwardshallowing, shoreface-to-shelf unit of the Bridport Sand Formation corresponds to a steeply-dipping (2-3°), delta-scale, progradational clinoform set that downlaps onto the topset of a similar progradational clinoform set in the Down Cliff Clay Member (Morris et al, 2006;Hampson et al, in press; Fig. 11BR).…”
Section: Example 2: Bridport Sand Formation Subaerial Delta and Down mentioning
confidence: 99%
“…; Ganges-Brahmaputra Rivers subaqueous delta (Kuehl et al, 1997;Palamenghi et al, 2011); Fly, Kikori and Purari Rivers (Walsh et al, 2004); Yellow River subaqueous delta (Yang and Liu, 2007); Mekong River subaqueous delta (Xue et al, 2010); Rhone River subaqueous delta (Fanget et al, 2014). While compound and subaqueous deltas are increasingly recognized on modern continental margins, their identification in ancient sedimentary records is more difficult, mainly for two reasons: the difficulty in pinpointing the position of the feeder system and the poor geometric resolution in depicting the low angle of muddy subaqueous progradations (Mellere et al, 2002;Morris et al, 2006;Hampson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The Jurassic Bridport Sand Formation, a close sedimentologic analog present onshore United Kingdom, contains similarly abundant calcite-cemented concretionary beds. These are observed at the outcrop to be laterally extensive (>80% areal coverage) along bedding planes and in a producing subsurface reservoir; their presence is marked by breaks in pressure and fluid saturation within seismically imaged clinoform sets (Morris et al, 2006;Hampson et al, 2014). Thus it appears probable that permeability barriers and baffles in the form of calcite-cemented concretionary layers occur along clinoforms in the Troll Field reservoir and could influence drainage patterns and recovery from the thin oil zone (Gibbons et al, 1993); this may have been recognized previously and shown to impact on well test interpretations (Lien et al, 1991;Haug, 1992).…”
Section: Example 2: Troll West Reservoir Sector Model Geological Settingmentioning
confidence: 99%